Gastroprotective effects of an aqueous extract of Cucurbita moschata seeds on ethanol induced gastric lesions in rats - MUNASINGHE, T.P.A.; DE FONSEKA, R.N.; RATNASOORIYA, W.D. (My University, 1993)
This study inve.<iligat,ed the polrntial gastroprotective activity of an aqueous extract ofC. moschaia seeds on ral using the lechnic/ne of elhatiot induced gastric lesions. The doses tested were 125, 250, ?75 and 500 mg/kg. The extract exhibited significant gastroprotective activity in a dose related manner. This activity was highly potent, EC^ being 93.75 mg